2000
DOI: 10.1159/000018848
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mesenteric and Portal Vein Thrombosis following Laparoscopic Nissen Fundoplication

Abstract: This case report describes superior mesenteric and portal vein thrombosis after laparoscopic Nissen fundoplication. As a thromboembolic prophylaxis, 2,500 IU of dalteparin was given preoperatively. After postoperative day 19, the patient experienced gradually increasing abdominal pain, mostly related to meals. Physical examination and laboratory tests were normal. CT scan revealed a portal and superior mesenteric vein thrombosis. Dalteparin and warfarin treatment was started, and symptoms relieved rapidly. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…6,8 Prompt treatment could also prevent progression to portal hypertension with risk of variceal hemorrhage. 5,9,10 Furthermore, early treatment could result in complete lysis of the clot, as was observed in our patient. Resolution of clot could be as early as four days, but could take up to one month.…”
Section: Discussionsupporting
confidence: 75%
“…6,8 Prompt treatment could also prevent progression to portal hypertension with risk of variceal hemorrhage. 5,9,10 Furthermore, early treatment could result in complete lysis of the clot, as was observed in our patient. Resolution of clot could be as early as four days, but could take up to one month.…”
Section: Discussionsupporting
confidence: 75%
“…18 Doppler ultrasound 5,6 or CT scan 4 showed complete resolution of portal thrombosis after one month with anticoagulation in the three cases reported of PVT after laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 85%
“…4,6 It has been suggested that the development of PVT requires a combination of several predisposing factors. 18 Valeri et al 5 reported a case of PVT after laparoscopic sple- nectomy in a patient with idiopathic thrombocytopenia and stated that the platelet increase, the blood stasis in the splenic vein, and the endothelial lesions secondary to splenectomy may all be contributing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumoperitoneum-associated mesenteric venous thrombosis has been reported after laparoscopic Nissen fundoplication [15][16][17] and laparoscopic hemicolectomy [18]. In two of the three reports of mesenteric venous thrombosis following laparoscopic Nissen fundoplication, the patients received dalteparin, 2500 U, 1 hr prior to the procedure.…”
Section: Discussionmentioning
confidence: 99%